(untitled) (Janaki Medical College Journal of Medical Science, 2024)
Background & Objectives: Potential health related risks and spread of communicable disease is one of the challenges of religious mass gatherings. With the rise of globalization, parts of Ayurveda are now popularized as a form of alternative medicine. In Nepal, Ayurveda medicine faces lots of challenges, and is under threat due to inadequate funding, ignorance of modern diagnostic technologies, and insufficient quality research. It is vitally important to continually monitor and promote Ayurveda in the modern era of allopathic medicine. Thus, this study aimed to identify the main complaints and advices on Ayurvedic medicine among pilgrims visiting Vivahpanchmi in Janakpurdham, Madhesh Province, Nepal. Materials and Methods: The information was gathered from the registration book of pilgrims who attended an Ayurveda health camp at Rangbhumi Maidan (Barahbigha) in December 2023, organized by the Ayurveda and Alternative Medicine center, Janakpurdham Sub Metropolitan office, Dhanusha, Madhesh Province. The extracted data were imported into MS Excel and SPSS 20 was used for analysis. Data were expressed in frequencies and percentage. Results: Of the 707 pilgrims, 97.7% were from India and 2.3% were from Nepal; 68.9% of the visitors were women and 31.1% were men. Out of all visitors, less than 10% were over 60, and more than half were between the ages of 41 and 60. Gastritis accounted for the highest percentage (45.9%), followed by joint pain, weakness, back pain (31.3%), and coughing (17.1%). Only 4.4% of people reported being constipated. Conclusion: The most common complaints from Pilgrims were related to gastritis (Amlapitta), which was followed by joint discomfort, weakness, and back pain (Vata). The possible ayurvedic advices and medications were provided and distributed among the pilgrims during Vivahpanchmi.